Functional Cause Analysis (FCA): uma adaptação do FMEA e FTA - Nascimento, Alex Maxwell Silva (2024)
Studies on satellites have progressed over the years, in line with technological advancements. Consequently, a concept of space systems, known as CubeSats, has emerged. This system concept represents projects that have been gaining market traction. However, despite this, this new systems perspective poses significant challenges, such as low success reliability, due to financial constraints, time limitations, and lack of experience among developers, especially in academic projects. Faced with these challenges, there is a need for methods and tools that facilitate the development and enhance the reliability of these systems, taking into account their difficulties. The objective of this work is to present a new approach to traditional tools for failure analysis, such as FMEA (Failure Modes and Effects Analysis) and FTA (Fault Tree Analysis), as a more agile alternative for failure analysis in projects with resource constraints. As a result of the challenges and needs previously identified, the FCA (Failure Criticality Analysis) was developed, an alternative tool designed to meet the specific demands raised, obtaining its validation through a case study on a CubeSat payload. The FCA has proven to be fully functional, as demonstrated in the case study, being as effective as traditional tools and providing approximately a 50% reduction in development stages and processes, thanks to its more objective and direct approach. In addition to the benefits obtained, the FCA has proven to be a versatile tool, applicable to any project requiring an easyto-use tool with reduced application time and that produces solid results, especially in teams with limited resources, thus promoting its success.